DAMPAK PENGGUNAAN FACEBOOK TERHADAP PERUBAHAN PERILAKU PADA IBU-IBU DI DESA MELIAU HULU KECAMATAN MELIAU, KABUPATEN SANGGAU - Genuina Mahesti Fortunata; Warneri Warneri; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the impact of using Facebook on behavior change among mothers in Meliau Hulu Village, Meliau District, Sanggau District. The general problem in this study is how the negative and positive impact of using Facebook on behavior change among mothers in Meliau Hulu Village, Meliau District, Sanggau District. The research method used is descriptive with a qualitative research form. Data collection techniques used observation, interviews and documentation. While the data collection tools used were observation guides, interview guides and documentation. The analysis in this study is presented in a descriptive qualitative manner using 4 informants who are active mothers of Facebook users in Meliau Hulu Village, Meliau District, Sanggau Regency. The results of this study indicate that Facebook has a negative impact on behavior change among mothers such as making Facebook a place of self-existence and show-off, lack of socialization with family and the surrounding environment, spreading self-portraits and personal problems as if making Facebook a place to vent. The positive impact on changes in the behavior of mothers, such as strengthening friendship, making Facebook a means of promoting merchandise, and using Facebook as an information medium as a substitute for newspapers or television. And changes in behavior that occur as a result of using Facebook are due to the emergence of boredom and also the desire to change or want to be better known.Keywords: Facebook, Behavior Change, Mothers.